Distance approximation using pivot point in narrow phase collision detection - Sulaiman, Hamzah Asyrani; Bade, Abdullah; Abdullah, Mohd Harun (2013)
Discrete and Continuous Collision Detection is two common fields in Collision Detection research area where it helps to determine time and point of contact when two object intersect. Each technique increase speed and accuracy of the simulation itself but depending on application, we need to have specific solution of collision detection technique. Most computer games and simulation maintain speed as the main important elements while others such as medical and mechanical simulation needs to have a very high precision collision detection technique. Thus, an algorithm for the optimal distance computation algorithm for continuous collision detection is shown in this paper. The basic idea is to use an AABB for both object triangles and creating a moveable origin point called Dynamic Origin Point (DyOP). DyOP created by using minimum and maximum point of both AABBs where it dynamically changes whenever the object move. This is a novel algorithm that works better than the previously known Gilbert Keerthi-Johnson algorithm and Lin-Canny algorithm where it helps to reduce the complicated test and implementation. We have shown that our technique is performed faster than the previous algorithms by increasing speed and nearly approximate the good distance between two nearly intersected triangles.